A preparation method and product of conductive concrete with high mechanical properties
By using the combination technology of graphite fiber and expandable graphite particles in high-strength concrete, the problem of poor interfacial performance between fiber and concrete is solved, and the improvement of high mechanical strength and conductive properties is achieved, while reducing costs.
Patent Information
- Application Number
- CN202211623751.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-12-16
AI Technical Summary
Among existing high-strength concrete, the interface performance between fiber and concrete is poor, resulting in a decline in mechanical properties.
A number of expandable graphite particles are bonded to the outer circumference of the conductive fiber to form graphite fibers, which are then mixed with the concrete raw material. After curing and energizing, the expandable graphite particles are heat-expanded to fill the gap between the fiber/concrete.
By filling the gaps and forming new conductive paths, interface performance and mechanical strength are significantly improved, while reducing resistance, improving conductivity and reducing production costs.
Smart Images

Figure CN115816601B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation process of high-strength concrete, belongs to the field of concrete, and in particular to a preparation method and product of conductive concrete with high mechanical properties. Background Art
[0002] As an inorganic non-metallic silicate material, concrete is widely used in the construction field. In the prior art, in order to improve the mechanical strength of concrete and obtain high-strength concrete (i.e., high mechanical performance concrete), foreign fiber materials are often added to concrete. This is also a common method. However, this method of directly mixing ordinary fiber materials into concrete has the following shortcomings:
[0003] In the obtained fiber / concrete composite material, there will be gaps between the fibers and the concrete, resulting in poor interface performance between the fibers and the concrete, thereby reducing the overall mechanical properties, such as strength.
[0004] The information disclosed in this background technology section is only intended to increase the understanding of the overall background of the application, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art already known to ordinary technicians in this field. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects and problems of poor interface performance in the prior art and to provide a method and product for preparing conductive and high mechanical performance concrete with good interface performance.
[0006] To achieve the above objectives, the technical solution of the present invention is: a method for preparing conductive concrete with high mechanical properties, the preparation method comprising the following steps:
[0007] The first step is to bond a plurality of expandable graphite particles to the outer periphery of the conductive fiber, and then leave it to stand for bonding and curing to obtain a graphite fiber;
[0008] Step 2: firstly, uniformly mix a plurality of graphite fibers with concrete raw materials, then add water and stir to obtain concrete slurry, and then allow the concrete slurry to stand and solidify to obtain a solidified body;
[0009] The third step: first connect the two ends of the solidified body to the circuit to energize the solidified body. After energization, the graphite fibers generate heat at a temperature of 200°C-500°C. When the expandable graphite particles in the solidified body expand due to heat, the conductive concrete with high mechanical properties can be obtained.
[0010] In the third step, when the heating is finished, the volume of the expandable graphite particles is 10 to 500 times that before the heating.
[0011] In the first step, the method of bonding a plurality of expandable graphite particles on the outer periphery of the conductive fiber is any one of the following:
[0012] The first method comprises spraying a binder onto the outer periphery of the conductive fiber to obtain a No. 1 viscous fiber, and then spraying expandable graphite particles onto the outer periphery of the No. 1 viscous fiber;
[0013] The second method is to first mix a binder with a plurality of expandable graphite particles to obtain a mixed solution, and then immerse the conductive fiber in the mixed solution, or spray the mixed solution onto the outer periphery of the conductive fiber in an atomized manner, or apply the mixed solution onto the outer periphery of the conductive fiber;
[0014] The third method is to immerse the conductive fiber in a binder first, then take out the conductive fiber to obtain a No. 2 viscous fiber, and then roll the No. 2 viscous fiber along the particle layer so that a plurality of expandable graphite particles are adhered to the outer side of the No. 2 viscous fiber, wherein the particle layer is composed of a plurality of expandable graphite particles.
[0015] The binder is any one of polytetrafluoroethylene solution, polyimide solution, aramid solution, bismaleimide resin, epoxy resin, phenolic resin, polyvinyl alcohol and polyacrylonitrile.
[0016] In the first step, the conductive fiber is any one of carbon fiber, carbon nanotube, metal fiber or composite fiber.
[0017] In the first step, the conductive fibers are chopped carbon fibers with a length of 1 mm to 5 mm, and the expandable graphite particles have a size of 0.1 mm to 1 mm.
[0018] The amount of the expandable graphite particles is 1wt%-10wt% of the weight of the concrete raw materials, and the amount of the conductive fibers is 1wt%-3wt% of the weight of the concrete raw materials.
[0019] The amount of the expandable graphite particles used is two to five times the weight of the carbon fibers.
[0020] In the second step, allowing the concrete slurry to stand and solidify to obtain a solidified body means allowing the concrete slurry to stand at room temperature for 3-30 days to obtain a solidified body.
[0021] A product, which is concrete, is prepared according to the above-mentioned method for preparing the conductive concrete with high mechanical properties.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. In the preparation method and product of a conductive concrete with high mechanical properties of the present invention, graphite fibers containing expandable graphite particles are first prepared, and then the graphite fibers are uniformly mixed with concrete raw materials, and then water is added and stirred to obtain concrete slurry, and then the concrete slurry is left to stand and solidify to obtain a solidified body, and finally the solidified body is energized to make the graphite fibers heat up, so that the expandable graphite particles in the solidified body expand due to heat, and then the conductive concrete with high mechanical properties is obtained. The advantages of this design include: first, by adding fibers such as graphite fibers to the concrete raw materials, the mechanical strength of the final product can be improved; second, when the graphite fibers can be added ... third, when the graphite fibers can be added to the concrete raw materials, the mechanical strength of the final product can be improved; fourth, when the graphite fibers can be added to the concrete raw materials, the mechanical strength of the final product can be improved; fourth, when the graphite fibers can be added to the concrete raw materials, the mechanical strength of the final product can be improved; fifth, when the graphite fibers can be added to the concrete raw materials, the mechanical strength of the final product can be improved; fifth, when the graphite fibers can be added to the concrete raw materials, the mechanical strength of the final product can be improved. When the expanded graphite particles are heated and expanded, the expanded volume can fill the gap between the fiber / concrete, thereby reducing the gap between the fiber / concrete, eliminating the defects in the prior art, and then enhancing the interface performance, so that the concrete strength is greatly improved; again, during the curing process, the concrete slurry will form certain bubbles and gaps, causing its mechanical properties to decline, and in this design, although the curing of the concrete slurry will still form bubbles or gaps, since the expandable graphite particles will expand after being heated, some bubbles or gaps will be occupied by the expanded graphite, thereby further improving the overall mechanical strength of the final concrete. Therefore, the present invention not only has better interface performance, but also can improve the mechanical strength of the final product.
[0024] 2. In the preparation method and product of a conductive and high mechanical performance concrete of the present invention, the carrier carrying expandable graphite particles is conductive fiber. When the conductive fiber and the expandable graphite particles bonded thereto are present in the solidified body together, the initial energization of the solidified body is the energization of the conductive fiber. However, after the conductive fiber is energized and heated, the expandable graphite particles bonded thereto will expand due to heat. This expansion can not only improve the interface performance and mechanical strength, but also become a bridge between adjacent conductive fibers, and can bridge adjacent carbon fibers, thereby forming a new conductive path, obtaining a larger number of conductive paths with a wider coverage, greatly reducing the resistance of concrete, and improving the conductive performance. At this time, continuing to energize becomes a network-type conduction, and the efficiency is greatly improved. In addition, the price of expandable graphite is extremely low, and thus, the addition of expandable graphite can reduce the use of conductive fibers and reduce the production cost. Even if the amount of conductive fibers is unchanged, the additionally added expandable graphite is also conducive to breaking through the permeation threshold of the conductive fibers and improving the overall cost performance. Therefore, the present invention not only has better conductive performance improvement, but also has lower production cost.
[0025] 3. In the preparation method and product of the conductive and high mechanical performance concrete of the present invention, the graphite fiber added to the concrete can be regarded as a mixture of expandable graphite and conductive fiber, and the expandable graphite will increase the mechanical strength of the final concrete after heating, which means that when obtaining the same strength concrete, the fiber content required by the design is far less than the fiber content required by the conventional fiber / concrete, and the price of expandable graphite is extremely low, so that the design has a lower production cost. Therefore, the production cost of the present invention is low.
[0026] 4. In the preparation method and product of the conductive and high mechanical performance concrete of the present invention, before the solidified body is electrified to make the graphite fiber heat up, the concrete slurry needs to be solidified instead of directly heat-treated. The reason is that the solidification of concrete requires a certain amount of water. If the concrete slurry is directly heat-treated, the water will be consumed quickly, which is not conducive to the final molding of the concrete, and may even crack, greatly reduce the mechanical strength, and also destroy the basis for the expandable graphite to play. Therefore, the present invention can ensure strong mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is an operation flow chart of the present invention.
[0028] Figure 2 It is a comparative schematic diagram of the effect of the graphite fiber on the fiber / concrete interface before and after expansion in the present invention.
[0029] Figure 3 It is a position comparison between the expandable graphite particles and the adjacent conductive fibers before and after expansion in the present invention. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0031] See also Figure 1 — Figure 3 , a method for preparing conductive concrete with high mechanical properties, the preparation method comprising the following steps:
[0032] The first step is to bond a plurality of expandable graphite particles to the outer periphery of the conductive fiber, and then leave it to stand for bonding and curing to obtain a graphite fiber;
[0033] Step 2: firstly, uniformly mix a plurality of graphite fibers with concrete raw materials, then add water and stir to obtain concrete slurry, and then allow the concrete slurry to stand and solidify to obtain a solidified body;
[0034] The third step: first connect the two ends of the solidified body to the circuit to energize the solidified body. After energization, the graphite fibers generate heat at a temperature of 200°C-500°C. When the expandable graphite particles in the solidified body expand due to heat, the conductive concrete with high mechanical properties can be obtained.
[0035] In the third step, when the heating is finished, the volume of the expandable graphite particles is 10 to 500 times that before the heating.
[0036] In the first step, the method of bonding a plurality of expandable graphite particles on the outer periphery of the conductive fiber is any one of the following:
[0037] The first method comprises spraying a binder onto the outer periphery of the conductive fiber to obtain a No. 1 viscous fiber, and then spraying expandable graphite particles onto the outer periphery of the No. 1 viscous fiber;
[0038] The second method is to first mix a binder with a plurality of expandable graphite particles to obtain a mixed solution, and then immerse the conductive fiber in the mixed solution, or spray the mixed solution onto the outer periphery of the conductive fiber in an atomized manner, or apply the mixed solution onto the outer periphery of the conductive fiber;
[0039] The third method is to immerse the conductive fiber in a binder first, then take out the conductive fiber to obtain a No. 2 viscous fiber, and then roll the No. 2 viscous fiber along the particle layer so that a plurality of expandable graphite particles are adhered to the outer side of the No. 2 viscous fiber, wherein the particle layer is composed of a plurality of expandable graphite particles.
[0040] The binder is any one of polytetrafluoroethylene solution, polyimide solution, aramid solution, bismaleimide resin, epoxy resin, phenolic resin, polyvinyl alcohol and polyacrylonitrile.
[0041] In the first step, the conductive fiber is any one of carbon fiber, carbon nanotube, metal fiber or composite fiber.
[0042] In the first step, the conductive fibers are chopped carbon fibers with a length of 1 mm to 5 mm, and the expandable graphite particles have a size of 0.1 mm to 1 mm.
[0043] The amount of the expandable graphite particles is 1wt%-10wt% of the weight of the concrete raw materials, and the amount of the conductive fibers is 1wt%-3wt% of the weight of the concrete raw materials.
[0044] The amount of the expandable graphite particles used is two to five times the weight of the carbon fibers.
[0045] In the second step, allowing the concrete slurry to stand and solidify to obtain a solidified body means allowing the concrete slurry to stand at room temperature for 3-30 days to obtain a solidified body.
[0046] A product, which is concrete, is prepared according to the above-mentioned method for preparing the conductive concrete with high mechanical properties.
[0047] The principle of the present invention is described as follows:
[0048] See also Figure 2 Before the expandable graphite in the graphite fiber expands due to heat, there is a gap between the fiber and concrete, which makes the interface weak and reduces the overall strength of the concrete. After the heat treatment, the expandable graphite expands (the expansion process is similar to blowing a balloon, first filling the gap above the graphite, and then spreading to both sides after touching the concrete above), filling the gap (the interface is mainly the degree of bonding between the fiber and concrete, the closer the contact between the two, the better the interface, there will be a small gap between ordinary fiber and concrete, so the interface performance is poor), causing the fiber and concrete to contact, reducing the gap between the fiber and concrete, thereby enhancing the interface performance, and greatly improving the strength of the final concrete.
[0049] See also Figure 3 After the expandable graphite particles in the present invention are heated (ie, the conductive fibers are heated), the expandable graphite particles expand, and the volume of the expandable graphite particles increases, so that they can bridge adjacent conductive fibers, thereby forming new conductive paths.
[0050] The concrete raw material in the present invention refers to a substance that can be left to solidify after adding water, such as any one of cement, stone, sand, and aggregate or any mixture thereof.
[0051] The "standing still for bonding and curing" in the present invention means that the expandable graphite particles are bonded to the outer periphery of the conductive fiber by a binder. When just bonded, the binder has a certain fluidity. In order to prevent a large number of expandable graphite particles from falling off when subsequently mixed with concrete raw materials, it is necessary to stand still for a certain period of time until the binder is cured and loses fluidity, thereby obtaining graphite fibers.
[0052] The "composite fiber" in "the conductive fiber is any one of carbon fiber, carbon nanotube, metal fiber or composite fiber" in the present invention refers to: a fiber having more than one component, at least one of which can conduct electricity and generate heat.
[0053] Embodiment 1:
[0054] See also Figure 1 — Figure 3 , a method for preparing conductive concrete with high mechanical properties, the preparation method comprising the following steps:
[0055] The first step is to bond a plurality of expandable graphite particles to the outer periphery of the conductive fiber, and then leave it to stand for bonding and curing to obtain a graphite fiber;
[0056] Step 2: firstly, uniformly mix a plurality of graphite fibers with concrete raw materials, then add water and stir to obtain concrete slurry, and then allow the concrete slurry to stand and solidify to obtain a solidified body;
[0057] The third step: first connect the two ends of the solidified body to the circuit to energize the solidified body. After energization, the graphite fibers generate heat at a temperature of 200°C-500°C. When the expandable graphite particles in the solidified body expand due to the heat, the conductive concrete with high mechanical properties can be obtained (preferably, when heating is completed, the volume of the expandable graphite particles is 10 times-500 times that before heating).
[0058] Embodiment 2:
[0059] The basic content is the same as that of Example 1, except that:
[0060] In the first step, the method of bonding a plurality of expandable graphite particles on the outer periphery of the conductive fiber is any one of the following:
[0061] The first method comprises spraying a binder onto the outer periphery of the conductive fiber to obtain a No. 1 viscous fiber, and then spraying expandable graphite particles onto the outer periphery of the No. 1 viscous fiber;
[0062] The second method is to first mix a binder with a plurality of expandable graphite particles to obtain a mixed solution, and then immerse the conductive fiber in the mixed solution, or spray the mixed solution onto the outer periphery of the conductive fiber in an atomized manner, or apply the mixed solution onto the outer periphery of the conductive fiber;
[0063] The third method is to immerse the conductive fiber in a binder first, then take out the conductive fiber to obtain a No. 2 viscous fiber, and then roll the No. 2 viscous fiber along the particle layer so that a plurality of expandable graphite particles are adhered to the outer side of the No. 2 viscous fiber, wherein the particle layer is composed of a plurality of expandable graphite particles.
[0064] Embodiment 3:
[0065] The basic content is the same as that of Example 1, except that:
[0066] The binder is any one of polytetrafluoroethylene solution, polyimide solution, aramid solution, bismaleimide resin, epoxy resin, phenolic resin, polyvinyl alcohol and polyacrylonitrile.
[0067] Among them, polyvinyl alcohol or polyacrylonitrile is the best and can achieve the greatest degree of elimination.
[0068] Embodiment 4:
[0069] The basic content is the same as that of Example 1, except that:
[0070] The conductive fiber is any one of carbon fiber, carbon nanotube, metal fiber or composite fiber, among which carbon fiber is the best.
[0071] Embodiment 5:
[0072] The basic content is the same as that of Example 1, except that:
[0073] The amount of the expandable graphite particles is 1wt%-10wt% of the weight of the concrete raw material, and the amount of the conductive fiber is 1wt%-3wt% of the weight of the concrete raw material. The amount of the expandable graphite particles is two to five times the weight of the carbon fiber. Among them, the comprehensive effect is best when the amount of the expandable graphite particles is 9wt% of the weight of the concrete raw material and the amount of the conductive fiber is 3wt% of the weight of the concrete raw material, which not only has high mechanical strength, but also has good conductive effect and low overall resistance value.
[0074] Embodiment 6:
[0075] The basic content is the same as that of Example 1, except that:
[0076] A product, which is concrete, is prepared according to the above-mentioned method for preparing the conductive concrete with high mechanical properties.
[0077] The above description is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiment. Any equivalent modifications or changes made by ordinary technicians in this field based on the contents disclosed by the present invention should be included in the protection scope recorded in the claims.
Claims
1. A method for preparing conductive concrete with high mechanical properties, characterized in that: The preparation method comprises the following steps: The first step is to bond a plurality of expandable graphite particles to the outer periphery of the conductive fiber, and then leave it to stand for bonding and curing to obtain a graphite fiber; Step 2: firstly, uniformly mix a plurality of graphite fibers with concrete raw materials, then add water and stir to obtain concrete slurry, and then allow the concrete slurry to stand and solidify to obtain a solidified body; The third step: first connect the two ends of the solidified body to the circuit to energize the solidified body. After energization, the graphite fibers heat up at a temperature of 200°C-500°C. When the expandable graphite particles in the solidified body expand due to heat, the expansion increases the volume of the graphite particles, thereby bridging adjacent conductive fibers to form a network-like conductive path, thereby obtaining the conductive concrete with high mechanical properties.
2. The method for preparing a conductive concrete with high mechanical properties according to claim 1, characterized in that: In the third step, when the heating is finished, the volume of the expandable graphite particles is 10 to 500 times that before the heating.
3. The method for preparing a conductive concrete with high mechanical properties according to claim 1 or 2, characterized in that: In the first step, the method of bonding a plurality of expandable graphite particles on the outer periphery of the conductive fiber is any one of the following: The first method comprises spraying a binder onto the outer periphery of the conductive fiber to obtain a No. 1 viscous fiber, and then spraying expandable graphite particles onto the outer periphery of the No. 1 viscous fiber; The second method is to first mix a binder with a plurality of expandable graphite particles to obtain a mixed solution, and then immerse the conductive fiber in the mixed solution, or spray the mixed solution onto the outer periphery of the conductive fiber in an atomized manner, or apply the mixed solution onto the outer periphery of the conductive fiber; The third method is to immerse the conductive fiber in a binder first, then take out the conductive fiber to obtain a No. 2 viscous fiber, and then roll the No. 2 viscous fiber along the particle layer so that a plurality of expandable graphite particles are adhered to the outer side of the No. 2 viscous fiber, wherein the particle layer is composed of a plurality of expandable graphite particles.
4. The method for preparing a conductive concrete with high mechanical properties according to claim 3, characterized in that: The binder is any one of polytetrafluoroethylene solution, polyimide solution, aramid solution, bismaleimide resin, epoxy resin, phenolic resin, polyvinyl alcohol and polyacrylonitrile.
5. The method for preparing a conductive concrete with high mechanical properties according to claim 1 or 2, characterized in that: In the first step, the conductive fiber is any one of carbon fiber, carbon nanotube, metal fiber or composite fiber.
6. The method for preparing a conductive concrete with high mechanical properties according to claim 1 or 2, characterized in that: In the first step, the conductive fibers are chopped carbon fibers with a length of 1 mm to 5 mm, and the expandable graphite particles have a size of 0.1 mm to 1 mm.
7. The method for preparing a conductive concrete with high mechanical properties according to claim 1 or 2, characterized in that: The amount of the expandable graphite particles is 1wt%-10wt% of the weight of the concrete raw materials, and the amount of the conductive fibers is 1wt%-3wt% of the weight of the concrete raw materials.
8. The method for preparing a conductive concrete with high mechanical properties according to claim 7, characterized in that: The amount of the expandable graphite particles used is two to five times the weight of the carbon fibers.
9. The method for preparing a conductive concrete with high mechanical properties according to claim 1 or 2, characterized in that: In the second step, allowing the concrete slurry to stand and solidify to obtain a solidified body means allowing the concrete slurry to stand at room temperature for 3-30 days to obtain a solidified body.
10. A product, characterized in that: The product is concrete, which is prepared according to the method for preparing a conductive concrete with high mechanical properties as described in claim 1 or 2.
Citation Information
Patent Citations
Conductive graphite grease for preparing conductive fibers and preparation method thereof as well as method for preparing cellulosic fiber by graphite grease
CN104064255A
Large-volume concrete and preparation method thereof
CN108793887A
Cited By
Preparation method of low-shrinkage conductive UHPC, UHPC and application method
CN122482750A